ENGLISH TOPONYMS IN SEMANTICO-STYLISTIC PARADIGMS, THEIR CORRELATIONS IN UKRAINIAN AND RUSSIAN TEXT - Онищенко, Ірина (Current Issues of Foreign Philology, 2021)
The article reveals English toponyms of antroposemic field and their correlations in Ukrainian and Russian text. It has been proved that the studies of stable expressive and stylistic functions of the word separately from its objective meaning is unreal as well as the studies of the meanings of the word without taking into consideration the possibilities of the word’s usage, that is, its stylistic range. Thanks to the origin of the expressive and stylistic functions in the word the tendency to the language’s diversity, expressiveness, and riches of its stylistic possibilities is manifested. In this case both the communicative and the expressive moments are closely connected with each other. It need hardly be emphasized that the basis of each statement is communication, but if the expressive statement is developing still it keeps the form that grew on the basis of the communicative function. Secondary derivative meanings reflect universal language’s tendency to economize its resources: one word in the system of the language may have a lot of derivative meanings that are formed on the basis of metaphor revaluation of the primary meaning. A great number of bright examples taken from literature prove the idea: stylistically marked toponyms are functioning as original individual author’s metaphors revealing new tendencies of the development of man’s cognitive abilities, the formation of the world’s figurative picture. Due to various functioning of toponyms the tendency to language’s diversity, its expressiveness, and riches of its stylistic possibilities is manifested. The appearance of stylistically marked toponyms can be explained by the origin of new realities in modern life as a result of constant development of human cognition that puts forward a lot of tasks before the language, the most important of which is to provide all spheres of life and man’s activities with new denominations. It means that toponyms “in general” and stylistically marked elements of the language unite the objective, emotional, expressive, functional and stylistic components that are in close coordinated interaction. Words with emotional colouring appear as a result of metaphor transfer and are based upon some motivating feature. In languages of different peoples, however, this motivation doesn’t always coincide, and it is quite natural as it is the result of national and cultural specific nature that is reflected in peculiarities of the lexical word stock of each language.